The Characteristics of English Linking Adverbials (Journal of the College of Languages (JCL), 2008)
Linking adverbials are used to organize and bridge together extended stretches of discourse to make the text coherent. They are explicit indicators of the communicative function of the sentence and writers use them to let their readers follow what has already been said and to help them anticipate what is about to follow.Linking adverbials include those relations of addition, enumeration, summation, apposition and so on. Through the use of these adverbials, the writer is able to organize and develop his ideas and help the reader follow him from one sentence to another. Thus, a linking adverbial is a semantic relation used to show the way in which what is to follow is systematically connected to what has gone before. So, they have anaphoric reference which is considered to be a logical reason to call them 'linking adverbials'.This paper gives a brief and clear idea about the most important characteristics of linking adverbials.